Effect of SnCl2 and SnCl4 precursors on SnSx thin films prepared by ultrasonic spray pyrolysis. (June 2017) - Hadef, Z.; Kamli, K.; Attaf, A.; Aida, M.S.; Chouial, B.
Abstract: Thin films of SnS x, semiconductors, have been successfully synthesized by ultrasonic spray pyrolysis technique, using two precursors namely: tin (II) chloride and tin (IV) chloride, respectively. The solutions were prepared by the dilution of different Sn molarities of the two precursors separately. The precursor molarities were varied from 0.04 to 0.07 mol/L, whereas that of S was fixed at 0.1 mol/L. The present work focuses on the effect of the different precursor's molarities on the nature and the properties of the prepared thin films in order to optimize the growth conditions. X-ray diffraction analysis reveals that the precursor's molarities alter the grain size of the prepared films, which varied from 8 to 14 nm and from 12 to 16 nm, according to the used precursor. The films analysis by SEM, shows that the SnS2 films are more dense and smooth than the SnS films. The composition of the elements is analysed with an EDX spectrometer, and the obtained result for M sn = 0.07 mol/L indicates that the atomic ratio of Sn to S is 51.57 : 48.43 and 36 : 64 for films synthesized from the first and second precursors respectively. Electrical measurements show that the conductivity behavior depends on the used precursors and their molarities.